2022
DOI: 10.1002/ldr.4460
|View full text |Cite
|
Sign up to set email alerts
|

Biogeography and ecological functions of root‐associated and soil fungi of Pinus sylvestris var. mongolica across different afforestation areas in desertified Northern China

Abstract: China has unquestionably led efforts to 'green' drylands, but an evaluation of the large-scale effects of afforestation in desert ecosystems mediated by soil microorganisms is lacking. The ecological functions of fungi are closely related to soil and plant health. Therefore, there is a lively interest in revealing the biogeographic patterns of root-associated (RAF) and soil fungal (SF) communities of Pinus sylvestris var. mongolica, a widespread evergreen tree endemic to Northern China. We revealed the communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 96 publications
0
5
0
1
Order By: Relevance
“…There was a protective and feedback interaction between the host root system and EM fungi, which is relatively stable ( 10 ), while the root micro-environment provides a stable habitat for EM fungi in host plants’ roots through a strong environmental filter ( 55 ). Moreover, the low percentages of Wilcoxina and Suillus compared with previous studies in the Mu Us Desert ( 7 , 33 , 36 ) suggest that Mongolian pine plantations in this region suffer from an acute deterioration process or perturbation, probably as a consequence of human and livestock activity and environmental degradation.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…There was a protective and feedback interaction between the host root system and EM fungi, which is relatively stable ( 10 ), while the root micro-environment provides a stable habitat for EM fungi in host plants’ roots through a strong environmental filter ( 55 ). Moreover, the low percentages of Wilcoxina and Suillus compared with previous studies in the Mu Us Desert ( 7 , 33 , 36 ) suggest that Mongolian pine plantations in this region suffer from an acute deterioration process or perturbation, probably as a consequence of human and livestock activity and environmental degradation.…”
Section: Discussionmentioning
confidence: 69%
“…Variations in the diversity index of EM fungi according to stand age were inconsistent across the different stages of the growing season. Previous studies on the relationship between EM fungal diversity and stand age also revealed that there was a clear relationship between EM fungal diversity and host status ( 36 ). We expected a higher abundance of the EM fungi in mature forests, as many authors have noted a lower-diversity EM fungal community in younger forests, which increases with the root system and stand development ( 37 ).…”
Section: Discussionmentioning
confidence: 84%
“…Furthermore, the root systems of plants in PG plots can form network‐like structures, which help increase soil aeration and permeability. This root structure can break up compacted soil layers, facilitating the flow of oxygen and water in the soil and thus improving soil aeration and drainage capacity (Zhao et al, 2023). In contrast, the root systems of shrubs and arbors are relatively concentrated and cannot achieve the network‐like structure of plants in the PG plot; thus, they are less effective at improving soil structure than the PG plot.…”
Section: Discussionmentioning
confidence: 99%
“…, 能与松科 等多种高等植物根系形成互利共生的紧密联系体, 是森林生态系统的重要组成部分 (Bennett et al, 2017;Sebastiana et al, 2018)。外生菌根真菌能够改 善土壤质量, 促进寄主植物对矿质养分和水分的吸 收利用, 抵抗干旱、 病害和重金属等环境胁迫, 对森 林生态系统的养分运输、生物多样性维护和生态系 统稳定至关重要 (Courty et al, 2008;Zhao et al, 2022a)。 外生菌根真菌群落具有高度的时空异质性, 受 环境因素和寄主特性的共同调控 (Miyamoto et al, 2018;Arraiano-Castilho et al, 2021;Ren et al, 2022)。 寄主偏好性决定了外生菌根真菌群落物种组 成, 土壤性质随林龄的变化驱动了外生菌根真菌群 落的时间动态模式 (Hupperts et al, 2017)。气候是外 (Hayward et al, 2015;Miyamoto et al, 2018), 多变 的气候破坏土壤养分平衡, 使外生菌根真菌竞争资 源 以 适 应 养 分 循 环 过 程 (Mundra et al, 2015;Goldmann et al, 2016)…”
Section: 根系、菌根共生体及相关微生物之间的重要媒介unclassified